CLASSIFICATION OF GAME TECHNOLOGIES IN PROFESSIONAL EDUCATION - Khafizova Mashkhura Aminovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article reveals the basic concepts of pedagogical technologies and considers games as one of the types of technologies. The article provides a definition of the game, motives, features and needs for game activity. The author presents the basic pedagogical foundations of the organization of game activity. The methodology of the article is based on the effective use of various modern pedagogical approaches, accompanied by gaming technologies in the study of Russian as a foreign language. The practical significance of the article lies in the possibility of further application of situational role-playing games, both in psychological and pedagogical activities and in the educational process.